Effects of Puerarin on the Prevention and Treatment of Cardiovascular Diseases - Zhou, Yan-Xi; Zhang, Hong; Peng, Cheng (Frontiers in Pharmacology, 2021)
Puerarin, an isoflavone glycoside derived from Pueraria lobata (Willd.) Ohwi, has been identified as a pharmacologically active component with diverse benefits. A large number of experimental and clinical studies have demonstrated that puerarin is widely used in the treatment of a variety of diseases. Among them, cardiovascular diseases (CVDs) are the leading cause of death in the world, and therefore remain one of the most prominent global public health concerns. In this review, we systematically analyze the preclinical investigations of puerarin in CVDs, such as atherosclerosis, cardiac hypertrophy, heart failure, diabetic cardiovascular complications, myocardial infarction, stroke and hypertension. In addition, the potential molecular targets of puerarin are also discussed. Furthermore,we summarize the clinical trails of puerarin in the treatment of CVDs. Finally, the therapeutic effects of puerarin derivatives and its drug delivery systems are overviewed.